Design and experiment of a human-machine cooperative Chinese wolfberry harvester - Pan, Chenghao; Cao, Yuxuan; Tian, Zhicheng; He, Jing; Mei, Song; Song, Zhiyu (International Journal of Agricultural and Biological Engineering, 2026)
Abstract: Against the backdrop of large-scale and high-quality development of the wolfberry industry, mechanized harvesting dominated by vibration-based picking methods still struggles to simultaneously achieve low fruit damage and accurate harvesting in the short term. Accordingly, human-machine cooperation has emerged as a feasible solution for Chinese wolfberry mechanized harvesting at the current stage. Aiming at the agronomic characteristics of traditional Chinese wolfberry cultivation, such as prone trunk deflection and ground-hugging fruiting branches, a human-machine cooperative inter-row tracked Chinese wolfberry harvester was developed to address the technical bottlenecks of harvesting equipment regarding high trafficability, high fruit collection rate and low fruit damage rate. The fruit catching devices on both sides of the harvester are adjustable in width and height to adapt to complex field conditions and enhance inter-row operation trafficability. The width adjustment enables the bilateral catching devices to close centered on tree trunks, effectively reducing fruit dropping loss. Based on the collision kinematics analysis and simulation concerning fruit falling height, catching plate inclination angle and buffer material selection, flexible fruit catching plates were designed to mitigate collision damage and realize low-damage fruit collection. Meanwhile, the conveying and obstacle avoidance mechanisms were optimized, and an integrated technical scheme of “catching-conveying-separating” fruit collection and wind separation was established, achieving an impurity removal rate of 97.5 % through pneumatic separation. Field performance tests were conducted to verify the driving stability and operational efficiency of the machine. The results demonstrated that the prototype could travel stably and perform in-situ steering on sandy loam and soft ground. Under typical working conditions, the immediate total fruit damage rate was approximately 2.27 %, and the 24-hour delayed damage rate reached 4.07 %. This research indicates that the proposed human-machine collaborative Chinese wolfberry harvester can fully meet the field operation requirements of Chinese wolfberry orchards and alleviate the labor shortage during the harvesting season to a certain extent. Key words: Chinese wolfberry; human-machine cooperative harvesting equipment; crawler-type harvesting platform; fruit catching and pneumatic separation DOI: 10.25165/j.ijabe.20261904.10678 Citation: Pan C H, Cao Y X, Tian Z C, He J, Mei S, Song Z Y. Design and experiment of a human-machine cooperative Chinese wolfberry harvester. Int J Agric & Biol Eng, 2026; 19(4): 79–87.